PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, DAN KOMITMEN ORGANISASI TERHADAP SLACK ANGGARAN PADA TATANAN CONTAINER - Mastuti, Nurul; Risa, Nurma (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2012)
This study provides empirical evidence that budgetary participation, budgetary emphasis and organizational commitment might be the factor to create budgetary slack at PT Masaji Tatanan Container. Respondents of this study are all manajers and supervisors that participate in preparation of the budget. The results indicate that budgetary participation and organizational emphasis are not positively influence for the creation of budgetary slack. But budgetaru emphasis is positively influence the creation of budgetary slack. Finally, suggestion for PT Masaji Tatanan Container is company should be concerned to manajemen control system while creating budget, since company using budget for assessment performance.